The "wisdom" of Pierre Charron an original and orthodox code of morality - Charron, Jean Daniel (North Carolina studies in the Romance languages and literatures ;, 1961)
This book is a reevaluation and a reinterpretation of Pierre Charron (1541-1603)--in particularLa Sagesse--and of the impact of his writings. Jean Daniel Charron sheds new light upon this great figure in French literature, and argues that he should be considered more important and original than previously thought.